Trends of influenza B during the 2010–2016 seasons in 2 regions of north and south Italy: The impact of the vaccine mismatch on influenza immunisation strategy - Andrea Orsi; Giuseppina Maria Elena Colomba; Fanny Pojero; Giuseppe Calamusa; Cristiano Alicino; Cecilia Trucchi; Paola Canepa; Filippo Ansaldi; Francesco Vitale; Fabio Tramuto (Human Vaccines & Immunotherapeutics, 2018)
Influenza A and B viruses are responsible for respiratory infections, representing globally seasonal threats to human health. The 2 viral types often co-circulate and influenza B plays an important role in the spread of infection. A 6-year retrospective surveillance study was conducted between 2010 and 2016 in 2 large administrative regions of Italy, located in the north (Liguria) and in the south (Sicily) of the country, to describe the burden and epidemiology of both B/Victoria and B/Yamagata lineages in different healthcare settings. Influenza B viruses were detected in 5 of 6 seasonal outbreaks, exceeding influenza A during the season 2012–2013. Most of influenza B infections were found in children aged ≤ 14 y and significant differences were observed in the age-groups infected by the different lineages. B/Victoria strains prevailed in younger population than B/Yamagata, but also were more frequently found in the community setting. Conversely, B/Yamagata viruses were prevalent among hospitalized cases suggesting their potential role in the development of more severe disease. The relative proportions of viral lineages varied from year to year, resulting in different lineage-level mismatch for the B component of trivalent influenza vaccine. Our findings confirmed the need for continuous virological surveillance of seasonal epidemics and bring attention to the adoption of universal influenza immunization program in the childhood. The use of tetravalent vaccine formulations may be useful to improve the prevention and control of the influenza burden in general population.